A Study in Complexity: Unintended Consequences of Multiple Stakeholders in the U.S. Presidential Election Process. Issue 1 (2nd January 2021) - Chasdi, Richard J.; Ronis, Sheila R.
ABSTRACT: In 2023, 3 years after the 2020 U.S. Presidential election, a select group of senior intelligence analysts from the National Security Agency (NSA), Department of Homeland Security (DHS), and the Office of National Intelligence met for a reunion at an undisclosed location in Virginia to recall their all-day meeting with the National Security Council (NSC) at the White House in May 2020, and to recount the watershed international events that lead to the election of President Joseph R. Biden, Jr.